Biophysical studies of cytokine receptor interactions - Li, J; Jiejin Li (2000)
﻿ The IL-6 family of cytokines includes IL-6, ciliary neurotrophic factor (CNTF), leukemia inhibitory factor (LIF), oncostatin M (OSM), cardiotrophin-1, and IL-11. Functioning in a pleiotropic and redundant manner, these cytokines play an important role in the regulation of complex cellular processes such as gene activation, proliferation and differentiation, by signalling through homo- or heterodimers of gp130. This thesis describes the characterization of the interactions between the cytokine oncostatin M (OSM) and the cytokine-binding homology region (CHR) of its receptor gp130. Three forms of OSM were expressed, the native form and two truncated forms. Both mutations were obtained by C-terminal truncation. The first, OSM185, has an 11 amino residue deletion and the second, OSM187, has a 9-residue deletion. A variety of biophysical techniques were applied to investigate the complex. Analytical ultra-centrifugation (AUC), surface Plasma Resonance (SPR) and isothermal titration calorimetry (ITC) studies indicated that the purified proteins were stable in monomeric form and can form a 1:1 complex with affinity in the 0.1 μM range. One of the C-terminal truncated forms, the 187 residues version, showed higher stability than the native OSM (196 residues), but still demonstrated similar binding properties to the gp130-CHR. A 15N and 13C double-labelled OSM187 sample was produced for NMR studies. Due to the size of these two proteins, OSM187 (21.5 kDa) and gp130-CHR (25.2 kDa), the NMR studies of the complex are challenging. Applying the TROSY technique, data were obtained from the labelled OSM187 when it is in complex with gp130-CHR. The data could be compared with the free form OSM187 and several shifted peaks were detected. The binding site mapping work has just begun. The characterized binding properties and methods established for sample preparation provide a solid starting point for later studies. The thesis also contains an exploratory study of interactions between interleukin-2 (IL-2) and the IL-2 receptor β chain.